IDEOLOGI TERORISME DAN AYAT 60 SURAT AL-ANFAAL (Sebuah Upaya Restorasi Pemahaman Makna Turhibun) - Ahmad Mukhlasin (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This article is regarding the root of terrorism ideology and how to overcome the act of the terrorism, in particularly, the suicide bomb. The verse 60 of Surah Al-Anfal is commonly recognized as the one of the base ideology of Moslem terrorists roomates which misunderstood by them. So that is why this article discusses the right of it too. The terrorism is could not be eradicated by military action only but also the continuous educational efforts, especially in understanding verses of Qor’an roomates missused and misunderstood by moslem terrorists.